PENGEMBANGAN MODUL MENULIS POSTER BERBASIS PEMBELAJARAN KOLABORATIF UNTUK SISWA KELAS IV SEKOLAH DASAR - Ningsih, Eci; Yulida Angraini; Andrea Rinaldo; Elyusra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aimed to develop a collaborative learning-based poster-writing module for fourth-grade elementary school students and to determine its effectiveness. The study employed the Research and Development (R&D) method using the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The research subjects consisted of one teacher and 28 fourth-grade students from SDN 09 Bengkulu Tengah. Data were collected through observation, interviews, needs assessment questionnaires, documentation, poster-writing performance tests, and student response questionnaires. The needs analysis results indicated that 82% of students struggled to understand poster-writing material, and 93% required a module featuring poster examples and group activities. The developed module incorporates poster concepts, writing steps, examples, exercises, and collaborative activities. Limited trial results showed an improvement in poster-writing skills, with the average score rising from 49.93 in the pretest to 79.04 in the posttest, yielding an N-Gain of 0.58 (moderate category). The Wilcoxon test revealed a significant improvement (p < 0.001), alongside a 90% positive student response. Thus, the collaborative learning-based poster-writing module is suitable for use as supplementary teaching material for fourth-grade Indonesian language instruction in elementary schools.